1998
DOI: 10.1080/02626669809492102
|View full text |Cite
|
Sign up to set email alerts
|

An artificial neural network approach to rainfall-runoff modelling

Abstract: This paper provides a discussion of the development and application of Artificial Neural Networks (ANNs) to flow forecasting in two flood-prone UK catchments using real hydrometric data. Given relatively brief calibration data sets it was possible to construct robust models of 15-min flows with six hour lead times for the Rivers Amber and Mole. Comparisons were made between the performance of the ANN and those of conventional flood forecasting systems. The results obtained for validation forecasts were of comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
242
0
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 601 publications
(246 citation statements)
references
References 16 publications
0
242
0
4
Order By: Relevance
“…Since the 1990s, artificial neural networks (ANN) (ASCE Task Committee, 2000a,b), which are based on the architecture of the brain and nervous system, were gradually used in hydrological prediction (cf. Dawson & Wilby, 1998;See & Openshaw, 2000;Hu et al, 2001Hu et al, , 2005Campolo et al, 2003;Cigizoglu, 2003;Wilby et al, 2003;Giustolisi & Laucelli, 2005;Sy, 2006). In this paper, an attempt is made to examine any possible improvement in forecasting accuracy by employing the support vector machine (SVM) model (Vapnik et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1990s, artificial neural networks (ANN) (ASCE Task Committee, 2000a,b), which are based on the architecture of the brain and nervous system, were gradually used in hydrological prediction (cf. Dawson & Wilby, 1998;See & Openshaw, 2000;Hu et al, 2001Hu et al, , 2005Campolo et al, 2003;Cigizoglu, 2003;Wilby et al, 2003;Giustolisi & Laucelli, 2005;Sy, 2006). In this paper, an attempt is made to examine any possible improvement in forecasting accuracy by employing the support vector machine (SVM) model (Vapnik et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…These include, among others, rainfall forecasting (French et al, 1992), multivariate modelling of water resources time series (Raman & Sunilkumar, 1995), modelling of rainfall-runoff processes (Hsu et al, 1995), flow forecasting (Zealand et al, 1999;Dawson & Wilby, 1998), and river level forecasting (See & Openshaw, 1999). The promising results due to the use of ANNs in water resources make them a feasible technique to be employed in this research.…”
Section: Artificial Neural Network (Anns)mentioning
confidence: 99%
“…Although ANNs have already been shown to produce river flow predictions well compared to conventional models (Crespo & Mora, 1993;Karunanithi et al, 1994;Hsu et al, 1995;Abrahart & Kneale, 1997;Dawson & Wilby, 1998;Abrahart & See, 2000;Tingsanchali & Gautam, 2000), their ability to capture high and low flows is restricted to the research environment (Minns & Hall, 1996), and they often overestimate or underestimate high and low flows (Dawson & Wilby, 1998;Campolo et al, 1999;Karunanithi et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Dawson & Wilby (1998), and Campolo et al (1999) suggested that the underestimation of peak flows could be attributed to a lack of information provided to the network, such as the antecedent rainfall. Karunanithi et al (1994) suggested that the problem could be alleviated by including more high-flow patterns in the training data sets, while Hsu et al (1995) proposed log-transformations of flow values to reduce the gap between the high-and low-flow conditions.…”
Section: Introductionmentioning
confidence: 99%